Pengaruh Metode Dakwah Sebagai Bentuk Bimbingan Rohani Islam Terhadap Ketenangan Jiwa Jamaah - Gustiana, Annisa Aulia; Aprillia, Fany Putri; Azizah, Nur (Institut Agama Islam Negeri Padangsidimpuan, 2023)
The da'wah method is a form of applying Islamic spiritual guidance. This preaching increases knowledge, draws closer to God, and provides peace of mind for the congregation. Indirectly, the da'wah method positively influences the congregation in terms of peace of mind. This study aimed to see the effect of the da'wah method on peace of mind in worshipers at Mushola 17 Kober Banyumas, Central Java. This study applied a quantitative approach. The stages of data collection in this study consisted of direct observation (observation), distributing questionnaires, and calculating questionnaires. This study applies two variables, the variable that influences (independent) the Da'wah Method and the variable that is influenced (dependent) by Serenity of the Spirit. The study results show that the effect of the da'wah method on peace of mind in the congregation at the 17 Kober Mosque is that the t count is 2.776, which is greater than the t table 2.160. Based on the analysis of the coefficient of determination, the R Square results are 0.372. These results indicate an influence of the da'wah method on peace of mind, namely 37.2%, while 62.8% of peace of mind is influenced by other variables not examined. It can be concluded that the da'wah method positively influences the peace of mind of the congregation at Mushola 17 Kober. This positive influence means that the higher the use of the da'wah method in the congregation of the 17th mosque Kober, the more it will affect the peace of mind of the congregation.